Penerapan Strategi Self Management Dalam Meningkatkan Disiplin Anak Usia Dini (Studi Pada RA DWP UIN Sunan Kalijaga Yogyakarta) - Zubaedah, Siti (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2015)
Discipline is required for early childhood, especially in RA in the process of learning activities are implemented. A few problems related to discipline facing early childhood was difficulty to manage themselves in preparing themselves and their requirements in the preparation and learning activities. This research is Aimed to identify the increasing of discipline in the learning for early childhood after having been implemented self -management strategies. This research object is RA DWP Sunan Kalijaga. The Methods of data collecting are observation directly to the target object of study namely students of RA. Based on observations show that self-management strategies are given to students of RA can improve the discipline of children in the course.